PENGARUH KEPERCAYAAN DIRI TERHADAP PENYESUAIAN DIRI PADA MAHASISWA YANG BERASAL DARI DESA - Fari Hussuba; Rafita Sari; Khaula Lutfiah Fariha; Amaliyah Aziza; Haskya Putri Anean Cuherminisa (Journal of Communication and Social Sciences, 2023)
This research aims to investigate and explore the self-confidence and adjustment of students from rural areas. Rural areas differ significantly from urban areas in terms of social, economic, and educational aspects. Students from rural areas often face challenges in adapting to new environments, such as higher education settings in urban areas. This study utilizes a quantitative research method by collecting data through questionnaires. The research sample consists of students from rural areas who are pursuing higher education at universities in the city of Palembang. This study makes an important contribution to understanding the factors that influence the adjustment of students from rural areas. The findings of this research can serve as a reference for educational institutions to develop supportive programs aimed at enhancing the self-confidence of students, especially those who experience a transition from rural to urban environments. By making efforts to improve self-confidence, it is expected that students can more easily adapt and overcome challenges in the new academic and social environment.